Computer aided intepretation of images produced by radiography - Zhao, Peng. (2008)
Non-destructive testing (NDT) is widely used in many fields. In the field of defect inspection, the X-ray technique is one of the most popular methods. Currently all the radiographs have to be stored as films and interpreted manually by an experienced interpreter. It is time and manpower consuming work. But most importantly different persons will make different decisions.